Environmental pollution reduction in cement industry for cocombustion of waste tyre and coal as a fuel - Patil, R. K.; Garnaik, Baijayantimala; Khond, M. P.; Nawale, L. G. (International Journal of Modern Engineering Research, 2012)
In recent years, there are several problems encountered in waste management system particularly waste tyre as well as coals. The energy generation on incineration provides large amount of polycyclic aromatic hydrocarbon (PAH) emissions which is the cause of major environmental threat. Therefore, the combustion of coal and tyre were carried out in cement industry in order to generate heat energy at 1300oC and the only remaining residue (steel powder) to enhance the strength of the cement. At the outset, the particle size of coal and tyre was cut into 63-75 and 180-212 µm respectively. Combustion experiments were conducted using Nelson reactor under controlled conditions in presence of air and also in presence of nitrogen gas (INOX) atmosphere. The temperature range was varied from 300-13000C and several fuel mass loading in the furnace, expressed in terms of bulk equivalence ratios in the range of 0.7-2.4. At fixed bulk equivalence ratios, as the furnace gas (Air) temperature increased the polycyclic aromatic hydrocarbon yields from both fuels decreased drastically, while the CO2 yields increased. At the highest temperature around 13000C, the effluent of combustion of both (coal and tyre) fuels was practically devoid of polycyclic aromatic hydrocarbon (PAH) (at a detection limit of 0.3 µg of a PAH component/g of fuel burnt). In order to understand the rate of thermal effect and morphology of co combustion material (coal and tyre), the preliminary results are very essential to explore. Therefore, the thermo gravimetric analysis (TGA) and environmental scanning electron microscopy (ESEM) were carried out and results of coal and tyre mixture at various temperature conditions will be highlighted.

Electrospun polycaprolactone/hydroxyapatite/ZnO nanofibers as potential biomaterials for bone tissue regeneration - Shitole, Ajinkya A.; Raut, Piyush W.; Sharma, Neeti; Giram, Prabhanjan; Khandwekar, Anand P.; Garnaik, Baijayantimala (Journal of Materials Science-Materials In Medicine, 2019)
Fabricating a bioartificial bone graft possessing structural, mechanical and biological properties mimicking the real bone matrix is a major challenge in bone tissue engineering. Moreover, the developed materials are prone to microbial invasion leading to biomaterial centered infections which might limit their clinical translation. In the present study, biomimetic nanofibrous scaffolds of Poly -caprolactone (PCL)/nano-hydroxyapatite (nHA) were electrospun with 1wt%, 5wt%, 10wt%, 15wt% and 30wt% of zinc oxide (ZnO) nanoparticles in order to understand the optimal concentration range of (ZnO) nanoparticles balancing both biocompatibility and osteoregeneration. The developed nanofibrous scaffolds were successfully characterized using scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy dispersive X-ray analysis (EDAX), contact angle, fourier transform infrared spectroscopy (FTIR), wide-angle X-Ray diffraction (WAXD), brunaueremmett Teller (BET) surface area and tensile testing. Biocompatibility of the developed scaffolds at in vitro level was evaluated by culturing MG-63 cells and investigating the impact on cell viability, proliferation, protein adsorption, alkaline phosphatase (ALP) activity and biomineralization. The PCL/nHA scaffolds exhibited a 1.2-fold increase in cell viability and proliferation, while incorporation of ZnO nanoparticles to PCL/nHA imparted antimicrobial activity to the scaffolds with a progressive increase in the antimicrobial efficacy with increasing ZnO concentration. The results of cell viability were supported by ALP activity and mineralization assay, wherein, PCL/nHA/ZnO scaffolds showed higher ALP activity and better mineralization capacity as compared to pristine PCL. Although, the PCL/nHA/ZnO scaffolds with 10, 15 and 30wt% of ZnO particles exhibited superior antimicrobial efficacy against both gram-negative (E. coli) and gram-positive (S. aureus) bacteria, a significant decrease in the cell viability and mechanical properties was observed at higher concentrations of ZnO namely 15 and 30%. Amongst the various ZnO concentrations studied optimal cell viability, antimicrobial effect and mechanical strength were observed at 10wt.% ZnO concentration. Thus, the present study revealed that the biomimetic tri-component PCL/nHA/ZnO scaffolds with ZnO concentration range of10% could be ideal for achieving optimal biocompatibility (cell proliferation, biomineralization, and antimicrobial capacity) and mechanical stability thus making it a promising biomaterial substrate for bone tissue regeneration. [GRAPHICS] .

Evaluation of biocompatibility of synthesized low molecular weight PLGA copolymers using zinc L-proline through green route for biomedical application - Giram, Prabhanjan S.; Garnaik, Baijayantimala (Polymers for Advanced Technologies, 2021)
Poly(lactide-co-glycolide) (PLGA) copolymers were synthesized by ring opening polymerization in presence of zinc proline and stannous octoate in bulk through green route and were designated as PLGA-1 and PLGA-2 respectively. These copolymers were characterized using NMR, SEC, DSC, X-ray and MALDI-TOF analysis. For the first time, the low molecular weight of PLGA (similar to 11,000 Da) was mainly targeted to explore acute oral toxicity in the presence of zinc L-proline and stannous octoate. The haemolysis and cell viability assay were carried out for in-vitro cytotoxicity assessment. Haemolysis assay of PLGA-2 was confirmed and haemolytic potential exceeded limit of American society of testing of material standard. The cell viability study using fibroblast cell lines (NIH3T3), exhibited statistically significant difference in results between PLGA-1 and PLGA-2. The acute toxicity study was performed in Balb/c mice for biomarker, hematological and histopathological analysis. No mortality was observed during the entire observation period, and no macroscopic change of the organs was observed in PLGA-1 treated group where PLGA-2 treated group showed sign of toxicity. The results obtained from in-vitro and in-vivo studies suggested that PLGA-2 was toxic whereas PLGA-1 was nontoxic in nature. Therefore, PLGA-1 can be regarded as biocompatible biomaterials for potential for drug delivery and biomedical application.
Keywords: OECD-420; poly (lactide-co-glycolide); ring opening polymerization; Stannous octoate; zinc L-Proline

Engineered PLGA core-lipid shell hybrid nanocarriers improve the efficacy and safety of irinotecan to combat colon cancer - Giram, Prabhanjan S.; Nimma, Ramakrishna; Bulbule, Anuradha; Yadav, Amit Singh; Gorain, Mahadeo; Radharani, Nalukurthi Naga Venkata; Kundu, Gopal C.; Garnaik, Baijayantimala (ACS BIOMATERIALS SCIENCE & ENGINEERING, 2024)
Keywords: BULK-POLYMERIZATION; Drug-delivery; LIPOSOMAL DOXORUBICIN